USING PICTURES TO IMPROVE WRITING A DESCRIPTIVE TEXT - Herkulanus Akim; Albert Rufinus; Yanti Sri Rezeki (Universitas Tanjungpura, 2017)
AbstractThe purpose of this thesis was to improve students’ descriptive text writing by using pictures of grade 10A of SMAN 1 Kayan Hulu in the academic year 2016/ 2017. From the pre-observation interview, the writer found that the students had problems in using present tense and in differentiating the generic structure of descriptive text. Then, most of them lacked imagination and felt difficult to transfer their thoughts onto writing. This research was conducted through Classroom Action Research in two cycles. The participants of this research were 32 students in class 10A. The writer used measurement and observation technique to collect the data. He found that the students still had some problems of their writing in the first cycle, including generic structure, simple present tense, and the media used. To solve the students’ problem, the teacher decided to give more explanation about the use of simple present tense and generic structure of descriptive text, the teacher also asked the students to bring a dictionary in order to help the students in constructing a sentence. As a result in the second cycle,the students could write a descriptive text with good grammar and organization. In the first cycle, the students’ mean score was 59.68, it increased to 73.59 in the second cycle. In conclusion, the use of pictures improved the students’ writing of descriptive text. Keywords: Descriptive Text Writing, Pictures, Classroom Action Research